CINWA (database of terminology for cultivated plants in indigenous languages of northwestern South America): introducing a resource for research in ethnobiology, anthropology, historical linguistics, and interdisciplinary research on the neolithic transition in South America - Urban, Matthias; Panchi, Evelyn Michelle Aguilar; Lee, Saetbyul; Brodetsky, Evgenia (Language Resources & Evaluation, 2023)
This article introduces CINWA, a freely accessible online database of terminology for cultivated plants in indigenous languages of South America based on FAIR principles for scientific data management and stewardship. In the pre-release version we present here, CINWA assembles more than 2700 terms from more than 60 indigenous languages of northwestern South America, and coverage will be continuously expanded. CINWA is primarily designed for use in historical linguistics to explore patterns of lexical borrowing that might be used as a proxy for tracing the pathways by which knowledge of individual cultivated plants and the associated know-how spread from speech community to speech community in pre-Columbian South America. In spite of intensifying research, this is still unclear for most cultivars as the locales of initial cultivation are heterogeneous and spatially diffuse. However, possible uses of the CINWA database are manifold and go beyond this research question. The database can be used as a resource for ethnobiological and comparative anthropological research on South American communities, South American agricultural ecosystems and practices, and for studies in lexical borrowing, language contact, and historical linguistics broadly.